FAKTOR PREDISPOSING, ENABLING, DAN REINFORCING YANG BERHUBUNGAN DENGAN KESIAPSIAGAAN PERAWAT RUMAH SAKIT JIWA DALAM MENGHADAPI BAHAYA KEBAKARAN - Yasmita Anis Astari; Daru Lestantyo; Ekawati Ekawati (Jurnal Kesehatan Masyarakat (Undip), 2020)
Psychiatric hospital is an institution plenary mental health services that is available for 24 hours. Psychiatric hospital has the potential for functional and structural disorders that high risk to cause the fatalities when burned. Preparedness in handling fire incidents is very important for nurses to have, because fires can occur any time and the role of nurse to caring for patients and as a red code officer at each shift. Quantitative research were conducted with cross sectional study design involving all UPIP nurses (Psychiatric Intensive Service Unit). Data were collected online using google form. Based on the results of research that using chi-square test obtained variables associated with nurse’s preparedness are knowledge (ρ-value = 0.026), attitude (ρ-value = 0.001), training and socialization of outages (ρ-value = 0.041) and supervision of HSE officers (ρ-value = 0.010). While variables not related to nurse’s preparedness in the face of fire hazard are age (ρ-value = 0.608), gender (ρ-value = 1,000), working period (ρ-value = 1,000), education (ρ-value = 0.179), availability of fire protection facilities (ρ-value = 1,000 = 0.282), affordability of fire protection facilities (ρ-value = 1,000), evacuation route instructions (ρ-value = 0.467), and management commitment (ρ-value = 0.467). The research suggest to the management of psychiatric hospital needs to establish HSE hospital organization also provision of fire protection facilities that are still lacking.